Strategies and Business Innovations for the Competitive Advantage of Hotel Business in Thailand - Thanapotivirat, Pornnapa; Insawang, Wanwisa Ploy; Sirichotnisakon, Chisnupong (RMUTI Journal Humanities and Social Sciences, 2025)
This article aims to analyze the business strategies and innovations for competitive advantage in the hotel industry in Thailand, focusing on creating experiences and enhancing service value for hotel businesses. This is considered a critical factor in ensuring the survival of hotel businesses in the digital era by presenting comprehensive marketing and public relations approaches. These include marketing through influencers' perspectives, as well as collaborations between hotels and other renowned businesses to create networks and expand customer bases. Additionally, business expansion by leveraging existing products' reputation and quality can transform them into new business models, increasing product and service value to establish a competitive edge. Therefore, the business innovation models, relying on new marketing and public relations strategies, serve as a key factor in generating revenue and profits for hotel operations in the digital era, while also enhancing customer satisfaction, which is the ultimate outcome of hotel business operations.